“The latter-day General Grant”: forceful federal power and civil rights - King, D; Lieberman, RC (Cambridge University Press, 2020)
Progress toward racial equality requires the engagement of the American state, centered in the presidency and the executive branch, and in fact is not possible without the state's direct and forceful intervention. The key to this transformation is what we call “Forceful Federalism,” a multidimensional understanding of the American state. Forceful Federalism has four essential dimensions: standard-setting, coercion, associationalism, and fiscal authority. These four processes rise and fall over time, each charting its own history and unfolding according to its own logic. These processes usually work against each other. But occasionally they align with each other so that the state can pursue and achieve even difficult and challenging policy aims in a focused way. We sketch the outlines of Forceful Federalism and demonstrate its explanatory power with a case study of Forceful Federalism in action: James Meredith's integration of the University of Mississippi in 1962. The Meredith case exemplifies the convergence of the four dimensions of Forceful Federalism and marks the first time the modern American state was thus mobilized on behalf of civil rights. The case offers suggestive evidence that Forceful Federalism was a necessary condition for the emergence of the Civil Rights State.